PENGEMBANGAN E-MODUL IPAS TERINTEGRASI STEM PADA MATERI SIKLUS AIR DI KELAS V SEKOLAH DASAR - Desi Marliani Rahmania; Ali Ismail; Rana Gustian Nugraha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The limited integration of interactive and contextual digital learning materials in Science and Social Studies (IPAS) instruction at the elementary school level remains a considerable obstacle in the implementation of the Merdeka Curriculum. A real-world-oriented learning approach is essential to foster students’ 21st-century competencies. This study aims to develop a STEM-integrated e-module on the water cycle topic for fifth-grade students in elementary schools. The research employed a Research and Development (R&D) methodology using the ADDIE development model, which comprises five stages: Analyze, Design, Develop, Implement, and Evaluate. Data were collected through interviews and questionnaires. The product was validated by five experts, including two media experts and three content experts. The validation results indicated that the e-module achieved an average score of 96,65% from media experts and 94% from content experts, resulting in a combined score of 95,25%, which falls into the “highly valid” category. The practicality of the e-module was assessed through individual trials (n = 3; 100%), small-group trials (n = 24; 87%), and large-group trials (n = 27; 81,75%), with an overall average score of 88.6%, classified as “highly practical.” These findings confirm that the developed STEM-integrated e-module is both valid and practical, and thus appropriate to be implemented as a digital instructional material in IPAS learning on the water cycle topic at the elementary school level.